NONLINEAR METAMORPHOSES OF INFORMATION SOCIETY DEVELOPMENT IN THE CONDITIONS OF GLOBAL BIFURCATION PERIOD - KyrychenkoМ. О. (The Journal of V. N. Karazin Kharkiv National University, Series Philosophy. Philosophical Peripeteias, 2017)
The actual problem based on the complexity of the study of information society that had been developing in the period of Global Bifurcation is analysing in the paper. Notised that in order to detect society’s nonlinear metamorphoses in the conditions of Global Bifurcation, new knowledge, new theoretical principles and ideas, new modern methodology, techniques and research algorithms are needed.The main aim of the article is the conceptualization of non-linear metamorphoses of information society development in the conditions of Global Bifurcation.Themethodology requires analysis of the current human developmentat the turning point of the nonlinear metamorphoses correspond to the synergetic methods and techniques. The principles of trialetics, interdisciplinary approach and socio-synergetic allows to the deeply understanding the non-linear metamorphosis of information society development in the conditions of Global Bifurcation are the basis of the methodology. It is proved that the information society development is the discrete social process, with a change of evolutionary and bifurcation stages in the context. The structural synergistic approach as an expression of an interdisciplinary approach to the information society development allows to penetration into the bifurcation process, which the national elite and political actors have a decisive influence on. When the Socio-Synergetic focuses on the bifurcation processes, the Structural-Synergetic methodology focuses on the transhistorical structures and societal bifurcation. The scientific novelty is associated with an appeal to the structural-synergetic methodology that has not been used for the information society analysis yet.Conclusion: societal patterns act as a probabilistic tendencies, that play an important role in the victory of dominant societal tendency (the structure-attractor) where the inverse mechanisms stimulated by charismatic leader works. Outcomes outputs – the social process is not predefined, and there are new opportunities for historical creativity at the point of bifurcation in front of society. The non-linear methodology contributes to the analysis of the information society ideology in the context of Global Bifurcation period.